2010
DOI: 10.1158/1055-9965.epi-10-0544
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Bladder Cancer Risk: a Meta-analysis

Abstract: Background: Selenium is considered to be an antioxidant, and its high levels have been inversely associated with cancer risk of several sites. This meta-analysis examined the relationship between levels of selenium measured in serum and toenails, and the risk of bladder cancer.Methods: A meta-analysis using data from seven published epidemiologic studies (three case-control, three nested case-control, one case-cohort) published before March 2010 was done to examine the association between levels of selenium an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 33 publications
0
63
0
2
Order By: Relevance
“…It is estimated that half of the western population can expect to develop at least 1 colorectal tumor by age 70 (2). Epidemiological evidence indicates that selenium (Se) status is inversely associated with cancer risk, and results from intervention studies show that high Se intakes effectively reduce the risk of mammary, prostate, lung, colon, and liver cancer (3)(4)(5)(6)(7)(8). Interest in this area was stimulated by the landmark finding that supplementation of free-living people with Se-enriched brewer's yeast with predominantly selenomethionine (SeMet), decreased the overall cancer morbidity by nearly 50% (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that half of the western population can expect to develop at least 1 colorectal tumor by age 70 (2). Epidemiological evidence indicates that selenium (Se) status is inversely associated with cancer risk, and results from intervention studies show that high Se intakes effectively reduce the risk of mammary, prostate, lung, colon, and liver cancer (3)(4)(5)(6)(7)(8). Interest in this area was stimulated by the landmark finding that supplementation of free-living people with Se-enriched brewer's yeast with predominantly selenomethionine (SeMet), decreased the overall cancer morbidity by nearly 50% (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The Se and Vitamin E Cancer Prevention Trial (SELECT) showed that Se in the form of SeMet (9) did not prevent prostate cancer. This is somewhat unexpected because the Nutritional Prevention of Cancer (NPC) trial found that with Se-enriched brewer's yeast, Se reduced cancer risk including lung, colon, and prostate cancers (4,5,7,8). It has been suggested that SELECT men generally were replete in Se at baseline (8)(9)(10), which may be at least in part contributing to the failure of L-SeMet to reduce prostate and other cancers (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although preclinical evidence suggests a benefit of antioxidant therapies, antioxidant use in clinical practice is limited and systematic reviews report mixed outcomes of antioxidants. Specifically, conditions investigated by systematic reviews include various cancers [29][30][31][32], diabetes [33,34], cardiovascular disease [35][36][37], and neurodegenerative conditions [38][39][40]. Thus future studies are required to provide robust evidence for the potential of specific pharmaceuticals and cellular therapies, such as hMSCs, as alternative sources of antioxidants to promote antioxidant use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis from seven epidemiological studies showed that the overall risk of bladder cancer was inversely associated with elevated levels of selenium in serum and toenail samples, with the greatest effect seen in women (Amaral et al, 2010). Additionally, Wallace et al showed no association of selenium levels in toenail samples with bladder cancer, it did find a significant association with moderate smokers and p53 positive cancers, suggesting selenium may affect the risk of bladder malignancies with specific p53 immunophenotypes (Wallace et al, 2009).…”
Section: Seleniummentioning
confidence: 99%